No indication of insulin resistance in idiopathic pulmonary arterial hypertension with preserved physical activity. Issue 6 (11th June 2020) - Nagy, Bence M.; Kovacs, Gabor; Tornyos, Adrienn; Svehlikova, Eva; Foris, Vasile; Nagaraj, Chandran; Kwapiszewska, Grazyna; Pieber, Thomas R.; Olschewski, Andrea; Olschewski, Horst
There is growing interest in metabolic profiling in pulmonary arterial hypertension (PAH) due to current findings suggesting significant metabolic changes causing pulmonary arterial remodelling and linking PAH to insulin resistance [1]. Such findings may have major impact on future diagnostic and therapeutic strategies for PAH. However, most studies have enrolled patients with severe disease whose reduced physical activity may have a profound effect on insulin sensitivity. Insulin resistance might not be a primary cause of severe remodelling of the small pulmonary arteries in idiopathic PAH http://bit.ly/3c8elot